The French Forest System and Its Effects on the Algerians and European Settlers (1830-1930) - elhamel, Abdel Moneim (The Algerian Historical Journal, 2026)
The forests in Algeria were distinguished by their diversity, vast area and different density among the three workers of Algeria. They were of vital importance to Algerian society for the requirements of daily life, such as agriculture, housing, cooking wood, heating, household appliances and traditional crafts. Since its occupation of Algeria, the French colonialism has looted its diverse wealth, and exploiting them for his benefit, as the forests were of great importance to the colonial administration, due to their economic and political dimensions and their strong connection to colonial interests and settlement. The objectives of the colonial administration are multifaceted, all of which are aimed at one goal, which is to deprive the Algerians of all the gains and benefits and bestow upon the settlers all their spoils.